Analisis Konsistensi Penerapan Konsep Sustainable Tourism Berdasarkan Pendekatan Blue Accounting dan Kebijakan Sustainable Development Goal No. 14 Pada Wisata Nikoi Island dan Cempedak Private Island : Sustainable Tourism - Novrina, Putri Dwi; Chandra, Rezario Febrianta; Nasution, Finalesvita Br (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The purpose of this study is to determine the consistency of the application of sustainable tourism based on the blue accounting approach and the sustainable development goals No. 14 policy on Nikoi Island Tourism and Cempedak Private Island. Constancy is assessed from the joining of Nikoi Island Tourism and Cempedak Private Island as a Long Rung Alliance Member, which requires each member to achieve 4C sustainable goals, namely conservation, community, culture, and commerce. Bleu accounting is assessed on activities related to five (five) pilot project focuses that represent various interests and stakeholders, namely: (1) fish species in waters; (2) coastal wetlands; (3) marine transportation; (4) phosphorus control; and (5) water sources. The method used in this research is the qualitative method. Data collection was carried out in two ways, namely through interviews and literature studies. Data processing techniques include checking, correcting, reviewing, and providing explanations for the results of interviews. Data analysis techniques include collecting data, reducing data, presenting data, and drawing conclusions. The result of this research is that Wisata Nikoi and Cempedak Private Island have consistently implemented the concept of sustainable tourism based on 4C activities that reflect five blue accounting projects and support the achievement of Sustainable Development Goal No. 14 policy.